Assessing the impact of drought stress and soil cultivation in chardonnay and xynisteri grape cultivars - Chrysargyris, Antonios; Xylia, Panayiota; Litskas, Vassilis D.; Stavrinides, Menelaos; Heyman, Lisa; Demeestere, Kristof; Höfte, Monica; Tzortzakis, Nikos G. (My University, 2020)
Cyprus has a long tradition in grape cultivation and wine making and grapevine is important for the sustainability of the agricultural sector, like in other Mediterranean areas. Water scarcity, which is projected to increase due to climate change, could negatively affect the sector. In this research, the effects of irrigation and tillage treatments on various aspects of vine growth and product quality (e.g., yield, physiology and quality attributes), were studied in Chardonnay and Xynisteri cultivars grown in clay soils in Cyprus. Regarding soil properties and water content, N and K were more abundant in the soil than P and through the growing period irrigation tended to increase electrical conductivity (EC) in the soil. Soil water content (volumetric) was 22%-27.5% and 13%-16%, when irrigation was applied or not, respectively. Vegetative soil cover occupied 50%-55% of the surface and contained species typically present in Mediterranean farms (e.g., Poaceae, Fabaceae and Brassicaceae). Tillage increased yield in Xynisteri (4-5 kg plant-1) but negatively affected other parameters such as chlorophyll levels (in Xynisteri). In combination with irrigation, tillage increased antioxidant activity in Chardonnay (assessed by FRAP and DPPH), at harvest. Total phenolics at harvest were higher in the grape juice of Xynisteri, compared to Chardonnay (30-40 and 20-25 mg GA g-1 fresh weight, respectively). Irrigation influenced phytohormone levels in the two cultivars. ABA increased in non-irrigated Xynisteri, reflecting an increased capacity to react towards water stress. Water stress is considered to increase polyphenols in grapes, but in the case of Xynisteri it seems that irrigation water is required to obtain better quality grapes as without irrigation volumetric water content (VWC) is close to the permanent wilting point. Titratable acidity and total tannins decreased in Chardonnay, when tillage and irrigation were applied. In addition, tillage and irrigation tended to elevate the pH of the grape juice. Tillage and irrigation on the other hand, had no effect on the levels of ascorbic acid and total anthocyanin content. The results of this research may help to select management strategies that support the adaptation of viticulture to climate change in Cyprus and other Mediterranean areas.
Keywords: Cultivation practices; Grape quality; Irrigation; Plant hormones; Tillage